Integrasi Aksiologi dalam Manajemen Pendidikan Islam - Burhanuddin, Cepi; Yunita, Patria (Indo-MathEdu Intellectuals Journal, 2026)
This study aims to examine and analyze in depth the axiology of Islamic Education Management (MPI) and its implications for the formation of Islamic character in the educational process. MPI axiology emphasizes the objectives and benefits of all managerial activities (planning, organizing, implementing, supervising, and evaluating) in order to achieve educational effectiveness. The method used in this study is library research, which involves collecting, reviewing, and analyzing data sourced from literature, journals, and books related to values, ethics, morality, and management in the context of Islam. The results of the study show that values in MPI have two tendencies, namely theoretical values that form systematic scientific principles, and practical values that are oriented towards the internalization of Islamic culture into the souls of educational subjects. The ethical and moral foundation of MPI is derived from Prophetic Values (Shiddiq, Amanah, Tabligh, Fathanah), which are used as universal guidelines in leadership and management. The main educational values are classified into I'tiqodiyah (faith), Khuluqiyah (behavior, including compassion), and Amaliyah (mahḍah and ghairu mahḍah worship). The implementation of this axiology must be in line with al-Dharuriyat al-Sittah (Maqasid Syariah) to ensure the achievement of maslahah, making Islamic education an investment for success in this world and the hereafter.